THE MEASUREMENT OF CHLOROPHYLL a CONCENTRATION IN THE COASTAL WATERS ADJACENT TO KARANGANYAR SHRIMP PONDS, TUGU SEMARANG - Agung Setiarto; Suradi . (JOURNAL OF COASTAL DEVELOPMENT, 1999)
In order to determine the extent of eutrophication due to pollution of organic matter from brackishwater shrimp ponds, on the north coast of Central Java, chlorophyll a and nutrient concentration were measured in near shore waters. It was revealed that chlorophyll a content in the study area were considerably high, ranging between 83 and 332 µg/l. The evidence of eutrophication was also supported by the relatively high level of nutrient, in which nitrate levels ranged between 1.295 and 2.060 mg/l and phosphate ranged between 0.093 and 0.270 mg/l. The relationship of chlorophyll a and nitrate indicated negative of chlorophyll a and phosphate also indicated negative correlation with regression : P = - 0.2587 Chl a + 0.1945. This suggests that the increase in chlorophyll a is accompanied by a reduction of both nitrate and phosphate, which may be caused by luxurious consumption of nutrient by phytoplankton in the surface water.